Supplementation Of α Tocopherol On Plasma Membrane Integrity Of Goat Sperm After Freezing - Sri Wahjuningsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
Problems that often arise in the process of freezing semen is destruction of the plasma membrane because the sperm membrane contains unsaturated fatty acids are highly susceptible to peroxidation damage. α-tocopherol is an antioxidant that reduce damage due to peroxidation. The purpose of the study was to determine α-tocopherol antioxidant supplementation in diluter on plasma membrane integrity after freezing process. Semen was collected using artificial vagina from goat aged 2 to 2.5 years in normal reproduction. The design used was randomized block design with treatment dose of a different α-tocopherol (0 grams, 0.2 grams, 0.4 grams, 0.6 grams) in 100 ml of extender. The results showed that the percentage to plasma membrane integrity equilibrated at a dose of 0.4 g (75.46%) was higher (P <0.05) compared with a dose of 0.0 g (73.78%), and the dose of 0.6 g (72.93%), but did not differ (P> 0.05 ) with a dose of 0.2 g (75.46%). Plasma membrane integrity examination results at post thawing at dose of 0.4 g (73.16%)was higher (P <0.05) than a dose of 0.0 g (69.8%), 0.2 g (71.53%), 0.6 g (70.7 %) respectively. It was concluded that supplementation of antioxidant α-tocopherol 0.4 ml is the best dose to maintain membrane integrity of semen frozen of goat.